Retrieval Practice Improves Recollection-Based Memory Over a Seven-Day Period in Younger and Older Adults - Guran, Catherine-Noémie Alexandrina; Lehmann-Grube, Jovana; Bunzeck, Nico (Frontiers in Psychology, 2020)
Retrieving information improves subsequent memory performance more strongly than restudying. However, despite recent evidence for this retrieval practice effect (RPE), the temporal dynamics, age-related changes, and their possible interactions remain unclear. Therefore, we tested 45 young (18-30 years) and 41 older (50+ years) participants with a previously established RP paradigm. Specifically, subjects retrieved and restudied scene images on Day 1; subsequently, their recognition memory for the presented items was tested on the same day of learning and seven days later using a remember/know paradigm. As main findings we can show that both young and older adults benefited from RP, however the older participants benefited to a lesser extent. Importantly, the RPE was present immediately after learning on Day 1 and seven days later, with no significant differences between time points. Finally, RP improved recollection rates more strongly than familiarity rates, independent of age and retrieval interval. Together, our results provide evidence that the RPE is reduced but still existing in older adults, it is stable over a period of days and relies more strongly on hippocampus-based recollection.